2016
DOI: 10.3390/cells5020028
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Rho GTPases of the RhoBTB Subfamily: Roles in Vesicle Trafficking and Tumorigenesis

Abstract: RhoBTB proteins constitute a subfamily of atypical Rho GTPases represented in mammals by RhoBTB1, RhoBTB2, and RhoBTB3. Their characteristic feature is a carboxyl terminal extension that harbors two BTB domains capable of assembling cullin 3-dependent ubiquitin ligase complexes. The expression of all three RHOBTB genes has been found reduced or abolished in a variety of tumors. They are considered tumor suppressor genes and recent studies have strengthened their implication in tumorigenesis through regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…S5). RHOBTB2 is a tumor suppressor that is upregulated during drug-induced apoptosis and inhibits AKT (29,30). Thus, its inactivation may contribute to drug resistance.…”
Section: Alk-dependent Mechanisms Driving Resistance In Alcl Cells Inmentioning
confidence: 99%
“…S5). RHOBTB2 is a tumor suppressor that is upregulated during drug-induced apoptosis and inhibits AKT (29,30). Thus, its inactivation may contribute to drug resistance.…”
Section: Alk-dependent Mechanisms Driving Resistance In Alcl Cells Inmentioning
confidence: 99%
“…44,118 The Rho domain of RhoBTB1 and RhoBTB2 contains the amino acid motifs required for GTP-binding but is around 18 residues longer and rich in charged residues. 120,121 The GTP-binding domain of RhoBTBs is expected not to hydrolyse GTP, because they do not have key amino acids required for GTP hydrolysis, including a glycine equivalent to G12 and a glutamine equivalent to Q61 in Ras. 121,122 It has been reported that the GTP-binding domain of RhoBTB2 binds to GTP in vitro, 120 but nothing has been published for RhoBTB1.…”
mentioning
confidence: 99%
“…120,121 The GTP-binding domain of RhoBTBs is expected not to hydrolyse GTP, because they do not have key amino acids required for GTP hydrolysis, including a glycine equivalent to G12 and a glutamine equivalent to Q61 in Ras. 121,122 It has been reported that the GTP-binding domain of RhoBTB2 binds to GTP in vitro, 120 but nothing has been published for RhoBTB1. RhoBTB1 and RhoBTB2 are also bigger than classical GTPases due to the presence of extra domains including 2 broad-complex, tramtrack, bric a brac (BTB) domains, which are conserved proteinprotein interaction domains.…”
mentioning
confidence: 99%
“…RhoU and RhoV have high intrinsic GDP/GTP exchange rates, so are unlikely to need GEFs for activation but could still be turned off by GAPs [ 1 , 4 ]. For two other members, RhoBTB1 and RhoBTB2, the Rho domains are quite divergent in sequence from other family members and they are unlikely to be regulated by GEFs or GAPs [ 5 ].…”
Section: How Are They Regulated?mentioning
confidence: 99%
“…The exception is the Rnd proteins, for which several new targets have been identified by yeast two-hybrid screening, although so far we know relatively little about the functional consequences of these interactions [ 7 ]. RhoBTB proteins have been shown to interact via their BTB domains with Cullin-3, a scaffold for ubiquitin ligase complexes, but again the functional role of this interaction is not clear [ 5 ]. A challenge for the future will be to identify the protein interactome for each Rho GTPase and to determine how their interactions change dynamically during cellular responses and vary between cell types and with external conditions.…”
Section: How Do They Signal In Cells?mentioning
confidence: 99%